2018
DOI: 10.1002/hyp.13289
|View full text |Cite
|
Sign up to set email alerts
|

Soil water content and temporal stability in an arid area with natural and planted grasslands

Abstract: Soil water content (SWC) is a key factor for successful vegetation restoration in arid and semiarid regions, and vegetation has significant influences on the spatial patterns and temporal dynamics of SWC. The aim of this study was to investigate the temporal stability of SWC under different restored grasslands in an arid hilly area of Central China. SWC was measured in the 0‐ to 300‐cm soil profile in the natural grassland (Stipa capillata) and three typical planted grasslands (Medicago sativa, Agropyron crist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…In addition, the number of sites showing temporal stability in SWC did not increase with increasing soil depth. This result is partially consistent with that of Huang et al (2018) (0–300 cm) but inconsistent with that of Zhu et al (2020) (0–70 cm).…”
Section: Resultssupporting
confidence: 62%
“…In addition, the number of sites showing temporal stability in SWC did not increase with increasing soil depth. This result is partially consistent with that of Huang et al (2018) (0–300 cm) but inconsistent with that of Zhu et al (2020) (0–70 cm).…”
Section: Resultssupporting
confidence: 62%
“…Many studies focused on the relationship between temporal patterns of soil moisture and soil depth within a wide variety of ecosystems (Gao & Shao, ; Grant et al, ; He et al, ; Huang et al, ; Lin, ; Liu et al, ). Although we found lower mean r s than those above reported studies, we also found a significant increase in stability with soil depth.…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of shallow water was particularly prominent in M. sativa grassland. Many studies have shown that leguminous plants consume more water than gramineous plants in arid and semiarid areas (Cui et al, ; Huang et al, ). Other studies have indicated that the roots of the leguminous plants ( Caragana korshinskii and M. sativa ) were deeply distributed and could consume more deep soil water (Huang, Tian, Wu, Liu, & Dang, ; Jia & Shao, ).…”
Section: Discussionmentioning
confidence: 99%
“…High yield requires more water and the presence of deep roots that absorb deeper soil water; and the different plant species have different transpiration rates (Siltecho et al, ; Wang et al, ; Wang et al, ). Previous studies have suggested that the root system of the leguminous grasslands was deeper, which resulted in a higher consumption of soil water than the consumption of the gramineous grasslands (Huang et al, ). This process could further aggravate the soil water deficit and hinder the sustainability of field grasslands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation